2008
DOI: 10.1038/bjp.2008.106
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of thromboxane receptors by diclofenac and lumiracoxib

Abstract: British Journal of Pharmacology (2008) 153, 1763; doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Gastrointestinal bleeding is a common adverse event of aspirin and NSAIDs [22] . Spontaneous nongastrointestinal tract bleeding in patients with no history of bleeding disorders treated with NSAIDs is regarded extremely rare, with intracerebral hemorrhage being the most serious bleeding complication [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal bleeding is a common adverse event of aspirin and NSAIDs [22] . Spontaneous nongastrointestinal tract bleeding in patients with no history of bleeding disorders treated with NSAIDs is regarded extremely rare, with intracerebral hemorrhage being the most serious bleeding complication [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is accepted that some NSAIDs besides to produce in vitro and in vivo inhibition of COX, have additional mechanisms of action [18,19,26,38,[40][41][42]. At this respect, the antinociception observed in the present study would be due to different mechanisms, activation of the nitric oxide-cyclic GMP pathway and ATP-sensitive-, voltage-dependent-, large-and small-conductance Ca 2+ -activated-K + channels [19] or the inhibition of TP receptors [24].…”
Section: Discussionmentioning
confidence: 59%
“…Likewise, it has been demonstrated that the analgesic activity of the combination of lidocaine with opioids (morphine, levorphanol, buprenorphine and endorphin-1) was synergistic in different administration pathways and assays [53][54][55][56]. Lumiracoxib may decrease the excitability of presynaptic neurons by the inhibition of TP receptor [24] and the activation of the nitric oxide-cyclic GMP pathway and K + channels [19]. Lidocaine may synergize with these effects through its ability to inhibit Na + and Ca ++ channels, and 5-HT 3 and NMDA receptors [45][46][47][48][49][50], which would reduce the excitability of presynaptic neurons and postsynaptic dorsal horn neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolated and perfused rat lung (IPL) has been used in our laboratory as a model for studying effects of various pharmacological interventions on lung mechanics and vasoconstriction [11,12]. Recently, the DustGun aerosol technology has been used to expose the IPL, via dry powder inhalation, to aerosols of drugs and toxicants [13][14][15].…”
Section: A C C E P T E D Article In Pressmentioning
confidence: 99%